Shutter Island [videorecording (DVD)] - Scorsese, Martin; DiCaprio, Leonardo; Ruffalo, Mark; Kingsley, Ben, 1943-; Williams, Michelle, 1980-; Sydow, Max von, 1929-2020-; Lehane, Dennis (Paramount Home Entertainment, 2010)
When U.S. Marshall Teddy Daniels arrives at the asylum for the criminally insane on Shutter Island, what starts as a routine investigation quickly takes a sinister turn. As the investigation unfolds and Daniels uncovers more shocking and terrifying truths about the island, he also learns there are some places that never let you go.